The Effect of Live Streaming Sales and Promotion on Impulsive Buying on ’Skintific’ Products on the TikTok Platform with Consumer Trust as an intervening variable - Dyta, Adytta Septi Yuliya; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The advancement of digital technology, particularly Live Streaming features and promotions on the TikTok platform, has significantly impacted consumers’ impulsive buying behavior. This study aims to analyze the effect of Live Streaming sales and promotions on impulsive buying behavior for "Skintific" products, with consumer trust as an intervening variable. A quantitative approach was employed, gathering data through an online survey of 100 consumers in the Jakarta area. Data analysis was conducted using SEM with SmartPLS. The findings indicate that Live Streaming and promotions have a significant positive effect on consumer trust. In turn, consumer trust significantly drives impulsive buying behavior. However, the direct effects of Live Streaming and promotions on impulsive buying are not significant. Indirect effects through consumer trust were found to be significant, underscoring the crucial role of trust in mediating these relationships. This study provides strategic implications for businesses to leverage Live Streaming and promotions to enhance consumer trust. Consequently, companies can encourage impulsive buying behavior by focusing on trust-building marketing strategies. These results highlight the importance of an integrated approach to creating engaging and spontaneous shopping experiences for consumers.